Synthesis of eggshell-derived hydroxyapatite and its deposition on titanium by electrophoretic method / Malihah Amiri Roudan - Malihah , Amiri Roudan (2018)
Hydroxyapatite (HA) is a well-known bioactive material, which has wide range of applications. One of the important purposes of using this material is the replacement of bone in human body, because of its similarity to bone structure and its excellent biocompatible nature. Calcium oxide is one of the main constituents of HA and can be obtained from various sources to synthesize hydroxyapatite. Some of these methods include sol-gel, hydrothermal and wet chemical method. Calcium can be found within the natural sources such as eggshell, seashell and animal bone and can be converted into calcium oxide thorough heat treatment process. In this study, synthesis and sintering behaviour of HA using eggshell as the source of Calcium has been conducted in a systematic manner. We synthesized HA using eggshell powder as a calcium oxide source via wet chemical precipitation method. Stoichiometric amount of Calcium oxide produced from calcining eggshell at 900 ℃, added to orthophosphoric acid, measured by stoichiometric ratio, then precipitated followed by aging overnight. Final solution was filtered and dried, then used as green powder to make the disc samples using 20 mm mold. The green samples were sintered in air at various temperatures ranging from 900 ℃ to 1400 ℃ at a ramp rate of 10 ℃ per minute and one hour holding time. The sintered samples were evaluated for HA phase stability, relative density, grain size, Vickers hardness and fracture toughness. X-Ray diffractometer (XRD) was used to analyze the phase composition. Field emission scanning electron microscope (FESEM) and energy dispersive spectroscopy (EDS) were carried out for microstructure characterization and elemental analysis, respectively. The XRD results indicated that the HA phase remained untill 1300 ℃. However a secondary phase of tricalcium phosphate (TCP) was observed at 1350 ℃ which was also confirmed by SEM examination. The relative density, Vickers hardness and fracture toughness were found to increase between 900 to 1100 ℃ and reached a plateau thereafter. A relatively density of 98.5%, high Vickers hardness of 5.9 GPa and fracture toughness of 1.09 MPam1/2 were achieved at 1250 ℃. The average grain size at this temperature was 2.5 μm. In the subsequent study, synthesized eggshell-hydroxyapatite was coated onto titanium substrate using electrophoretic deposition technique. Different voltage, current, time and weight were tested to determine optimum parameter for obtaining a crack free coated film. Coated samples were then sintered in a tube furnace at various temperatures under argon atmosphere. Analysis of the samples showed a homogenous and uniform HA coating. XRD analysis revealed that the HA phase was stable after sintering up to 1050℃. Cross section view of the coated samples confirmed good adhesion between coated layer and substrate. Overall, this research has demonstrated the viability of producing highly crystalline, phase pure hydroxyapatite from bio-waste eggshells and applying it as a coating material onto titanium. The synthesized hydroxyapatite had a stoichiometric Ca/P ratio of 1.67 without compromising on the thermal stability of the HA phase and the sintered eggshell-derived HA body exhibited excellent mechanical properties suitable for biomedical application.